Trade and Cross-Border Data Flows - Casalini, Francesca (OECD Trade Policy Papers, 2019)
The ubiquitous exchange of data across borders has given rise to a range of concerns by governments and citizens about some of the effects of so much information being collected and used, often without the knowledge of data subjects. This has led countries to condition or prohibit the transfer of data abroad, affecting trade in the process. This paper develops an indicative taxonomy of domestic approaches to cross-border data flow regulation and local storage requirements; it then surveys international instruments that address the question of international data transfers. The paper then examines the issues that data flow restrictions might raise for consumers and businesses. Against this backdrop, the paper highlights the challenge of finding balance between ensuring that important objectives, such as consumer privacy and security, are met while maintaining the benefits from free flows of data, including the benefits from increased and more inclusive digital trade